The Role of Neck Musculature in Traumatic Brain Injuries in Older Adults: Implications From Sports Medicine - Wood, Tyler A.; Morrison, Steven; Sosnoff, Jacob J. (Frontiers in Medicine, 2019)
Traumatic brain injuries (TBIs) are common and serious injuries to older adults. The majority of TBIs in older adults are sustained when the head impacts the ground or other surface during a fall. While several non-modifiable risk factors have been identified for fall-related TBIs in older adults, there still remains a dearth of knowledge surrounding modifiable risk factors. Thus, this significant knowledge gap warrants an investigation into research across disciplines. The sports medicine literature has examined several modifiable risk factors to prevent a mild form of TBI known as concussion. While this research has identified several risk factors, one particular risk factor may have potential implications to fall-related TBIs in older adults. The sports medicine literature has shown that decreased neck strength and slower neck muscle activation are significant predictors for sports-related concussion. Similarly, older adults experience age-related declines to neck muscle strength and muscle activation. Consequently, these age-related declines to the neck musculature may result in the inability of older adults to control their head during a fall, which results in greater impact forces being transmitted to the brain and increases the risk of TBI. This perspective article assesses the sports medicine literature related to the implications of neck strength and muscle activation in sports-related concussion, discusses age-related declines to neck strength and muscle activation, and highlights the potential impact of the neck musculature on fall-related TBIs in older adults.